What to examine in youth climbing athletes: Yearly examination of the German Climbing Team and its consequences - Schöffl, I.; Lutter, C.; Schöffl, V. (Sportverletzung Sportschaden, 2019)
Objective: This article presents the results of the yearly medical examination performed on all our national climbing athletes in 2016 and 2017.